If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 2h + h Combine like terms: 2h + h = 3h 42 = 3h Solving 42 = 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. 42 + -3h = 3h + -3h Combine like terms: 3h + -3h = 0 42 + -3h = 0 Add '-42' to each side of the equation. 42 + -42 + -3h = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -3h = 0 + -42 -3h = 0 + -42 Combine like terms: 0 + -42 = -42 -3h = -42 Divide each side by '-3'. h = 14 Simplifying h = 14
| 13m+7+2n-8m-3= | | f(x+3)=4x^2+3x-4 | | x/7-14=5 | | x^5-x^3-1=0 | | 48=2g+g+3g | | 16.2/x=9 | | (3n^2)-n-954=0 | | 5i(13-8i)= | | 30/n=8 | | 5x+2y+6+4y+2x-9= | | 3056890000-15000000x=300000000000 | | -10x^2+49x-12=0 | | (x+3)+y=180 | | -5.5=1.1 | | ×/2-4=-12 | | 9-5(2x*4-3)=-28 | | a+2b+b-8-5a= | | -1=n/14 | | 40+5+7n=101 | | x+7+4x+y+5= | | 7v-8/3=3v-7/6=4 | | C=1.25n | | 2x(2x+1)=0 | | .8-4(y-1)=.2+3(4-y) | | 1/3*-3/2 | | G(k)=12-5k | | -5=-2+2y | | 4y^2+32y+64=0 | | V(squared)+x=w(squared) | | (2*x)-sin(2*x)=10 | | 13a+8+8a+2= | | 2=2*-5-1 |